Spatiotemporal variability and climate teleconnections of global ocean wave power - Cao, Chuanchuan; Chen, Ge; Qian, Chengcheng; Shang, Jie (Frontiers in Marine Science, 2022)
Climate change impacts have driven a transformation of the global energy system. The utilization of renewable energies is required to meet energy demands while protecting the environment. Wind-generated waves, carrying energy from the atmosphere, are a possible energy supply. However, global and long-term variability in wave resources due to the effects of climate change remain uncertain. This study quantified the spatiotemporal patterns and availability of global wave power (GWP) based on the ERA5 hourly and monthly reanalysis products, spanning from 1979 to 2020. The most promising wave resources appeared centralized in the westerlies of both hemispheres, and the wave power exhibited a “rich-get-richer” trend in the Southern Ocean, dominating the overall distribution and variability of GWP. Significant seasonal and interannual oscillation trends in GWP were observed, but with little variations on daily and hourly time scales. We found the average GWP in ERA5 products increased by 12.89% suddenly in 1991, mainly caused by the beginning of altimeter assimilation. This also implies the potential underestimation of wave fields in the modeling results before the advent of altimeter. In the altimeter era, annual GWP exhibits (quasi-) decadal oscillation (variation near ±4%), which differed from the monotonous increases previously reported. An analysis and source tracing based on the climate teleconnections indexes revealed that the primary climate driver of the variability was the Southern Annual Mode (r = 0.84). This study provides scientific guidance for wave power utilization and helps deepen our understanding of air-sea interactions.